Skenario Film “Genius dari Syurga”: Peran Ayah dalam Pengembangan Anak Autisme melalui Struktur Tiga Babak - Nabilla Afiya Rizka; Dani Manesah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This article discusses the method of creating the screenplay for the film "Genius from Heaven," highlighting the role of fathers in the development of children with autism through a three-act structure. The creation method involves preparation, elaboration, synthesis, realization, and conclusion stages. The author conducts research, selects references from related films, and applies ideas with a three-act structure. The concept of creating this work includes the use of the dynamic character method and a three-act structure to build conflict and climax in the story. Analysis shows how the pressure from the father, changes in the behavior of the main character, Dino, and the father's awareness of his child's talent influence the dramatic dimension of the film. Technically, this article discusses the pre-production, production, and post-production stages, as well as production design, including work identity, film format, duration, language, and film goals. This film aims to provide insight to the public on educating children with special needs and demonstrates that behind someone's shortcomings, there are certainly strengths or unique talents.